Visa Policy as Migration Channel, Ireland - QUINN, EMMA (European Commission, 2011)
An Irish visa is a form of pre-entry clearance to travel to a point of entry to the State only. Whether or not the visa carries any legitimate expectation of entering the State has been debated in the courts. Ireland and the UK lie outside the Schengen zone and the issuing of both short and long-term visas is a national competence. Within the Schengen zone, the regulation of short-term visas falls within the competence of the EU, while long-term visa policy is set by the Member State. The Schengen short-stay regime concerns visas, issued by a Member State, which allow Third Country Nationals to enter that Member State, or several Member States, for stays not exceeding three months per six-month period. The Irish system is essentially discretionary, whereby the Minister for Justice and Equality1 decides whether or not to grant applications for visas; exceptions relate to beneficiaries of EU Treaty free movement rights.
PUBLISHED
Keywords: Public Policy; Migration; European Union